The effect of instructing mothers in attachment behaviors on short-term health outcomes of premature infants in NICU - Narges Abbasinia; Zahra Akbarian Rad; Mojtaba Qanbari Qalehsari; Hemmat Gholinia; Afsaneh Arzani (Wolters Kluwer Medknow Publications, 2023)
BACKGROUND: The birth of a pre-mature infant and subsequent hospitalization and separation from the family can impair maternal and neonatal attachment and quality of maternal care. This study aimed to assess the effect of instructing mothers in attachment behaviors on short-term health outcomes of pre-mature infants admitted to neonatal intensive care units (NICUs). MATERIAL AND METHODS: In this quasi experimental study, 80 mothers of pre-mature infants who were admitted to NICUs at two referral health centers in northern Iran were studied in two groups in 2018. Attachment behaviors were taught to mothers in the test group during four consecutive sessions. Mother-infant attachment behaviors were evaluated at both the beginning and the end of this study using a checklist derived from Avant's Maternal Attachment Assessment Strategy. Moreover, infants' short-term health consequences were investigated in two groups. SPSS 18 statistical software was used for data analysis. RESULTS: On average, it took respectively 34.90 ± 12/65 and 31/15 ± 14/35 days for the infants in the control and the intervention group to reach full oral feeding and 38/5 (38/4-42/11) and 37 (31/85-42/14) days to gain the minimum weight required for discharge. Moreover, the mean length of stay for the infants in the control and the intervention group was 41/80 ± 13/86 and 39/02 ± 16/01 days, respectively (P > 0/05). CONCLUSION: Instructing mothers in attachment behaviors clinically improved short-term health-related outcomes. Hence, this intervention is recommended to be incorporated in the care program for mothers with pre-mature infants.